Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Manufaktur Periode 2016 – 2018 - Lorenzo Salim, Elizabeth Sugiarto Dermawan (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The research was conducted with the aim of obtaining empirical evidence about the effect of dividend policy, liquidity, leverage, and firm size on the firm value listed on Indonesia Stock Exchange (IDX) in 2016-2018. This study uses data from financial statements published on the IDX’s official website and the company’s website. The research technique used was purposive sampling with total of 41 samples of manufacturing companies. This study uses a quantitive approach. The results of this study indicate that dividend policy has no significant effect on firm value. Liquidity and leverage have a positive and not significant effect on firm value. Firm size has a positive and significant effect on firm value.